Multiculturalism in Southeast Asia: A Comparative Analysis of Practices and Policy Implementation in Indonesia and Malaysia - Mudzill, Al; Munandar, Aris; Nuratika (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines and compares the practice of multiculturalism in Indonesia and Malaysia by situating it within their respective historical trajectories, policy frameworks, and implementation patterns in social and educational contexts. The research employs a qualitative library research design, drawing on relevant scholarly literature in the social sciences, religious studies, and the humanities. Data were analyzed using content analysis and a comparative approach, involving data reduction, data display, and conclusion drawing/verification. The findings indicate that multicultural practices in Indonesia and Malaysia exhibit both similarities and differences shaped by each country's historical, cultural, and political contexts. In Indonesia, multiculturalism is grounded in the national motto Bhinneka Tunggal Ika, whereas in Malaysia it is articulated through the principle of unity embodied in the Rukun Negara. At the policy level, Indonesia constitutionally recognizes diversity through inclusive measures, such as the public recognition of religious holidays and support for the preservation of local cultures. In contrast, Malaysia adopts a National Cultural Policy, which some groups have criticized for its limited sensitivity to cultural diversity. Linguistically, Indonesian functions as a unifying national language across diverse ethnic groups, while Malaysia recognizes Malay, English, and Chinese as official languages, reflecting its multicultural composition and educational arrangements. In terms of religion, Indonesia formally acknowledges and protects multiple religions and the rights of religious minorities. In contrast, Malaysia grants Islam a privileged position as the state's official religion.